2013
DOI: 10.1609/aimag.v34i3.2485
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Conversational Intelligent Tutoring Systems

Abstract: We report recent advances in intelligent tutoring systems with conversational dialogue. We highlight progress in terms of macro and microadaptivity. Macroadaptivity refers to a system’s capability to select appropriate instructional tasks for the learner to work on. Microadaptivity refers to a system’s capability to adapt its scaffolding while the learner is working on a particular task. The advances in macro and microadaptivity that are presented here were made possible by the use of learning progressions, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 34 publications
1
66
0
11
Order By: Relevance
“…The rest 20 articles focused on real world NLP-related applications, though no prototypical tasks were explicitly represented. For example, Rus et al [44] reported advances in intelligent tutoring systems with conversational dialogue, where each system could employ many complex NLP related tasks but not explicitly stated.…”
Section: Figure 3 Prototypical Tasks Commonly Studied In Nlp Researchmentioning
confidence: 99%
“…The rest 20 articles focused on real world NLP-related applications, though no prototypical tasks were explicitly represented. For example, Rus et al [44] reported advances in intelligent tutoring systems with conversational dialogue, where each system could employ many complex NLP related tasks but not explicitly stated.…”
Section: Figure 3 Prototypical Tasks Commonly Studied In Nlp Researchmentioning
confidence: 99%
“…DeepTutor integrates verbal contributions and problem-based assessment into the detection of learner states by using conversation and short multiple-choice tests to diagnose learning states (Rus et al 2013c). The system maps student statements and problem-solving activity to different states of understanding each concept.…”
Section: Learning Progressionsmentioning
confidence: 99%
“…AutoTutor and related systems in the family have tutored computer literacy (Graesser et al 2004a), conceptual physics (Graesser et al 2003a;Rus et al 2013c;VanLehn et al 2007), biology , critical thinking (Halpern et al 2012;Hu and Graesser 2004;Millis et al 2011), and other topics. AutoTutor approaches have also been extended to push the boundaries of the tutoring interaction, examining the impact of incorporating affect (AutoTutor-AS; D'Mello and Graesser 2012a), gaze focus (GazeTutor; D 'Mello et al 2012), metacognitive skills (MetaTutor; Azevedo et al 2010), and 3D simulations (AutoTutor-3D; Graesser et al 2005a).…”
mentioning
confidence: 99%
“…In order to better compare potential trade-offs between learning gains and training time, we define the efficiency of training for a particular student as the ratio of assessment score over total time spent during training (in minutes). The mean efficiency ratings (score/min) for each of the training methods were 8.44 for multiple choice format, 5.16 for natural language, and 5.52 for natural language without feedback. A oneway ANOVA showed that the difference between these efficiencies is significant (F(2,130) = 11.3, p < 0.001).…”
Section: Efficiencymentioning
confidence: 99%
“…Physics education, in particular, has an impressive pedigree of development -including ANDES/ATLAS [1], the AutoTutor series [2,3], Cordillera [4], and most recently Deep Tutor [5]. These computer tutors, using various natural language methodologies and to significant levels of success, have tackled physics topics such as forces, kinematics, Newton's laws, and energy conservation.…”
Section: Introductionmentioning
confidence: 99%